2017
DOI: 10.4103/1008-682x.180798
|View full text |Cite
|
Sign up to set email alerts
|

PSCA, Cox-2, and Ki-67 are independent, predictive markers of biochemical recurrence in clinically localized prostate cancer: a retrospective study

Abstract: Prostate cancer is the second most common male cancer, with half of all patients going on to develop metastases. To better identify patients at high risk for prostate cancer progression and reduce prostate cancer-related mortality, improved prognostic factors are required. In this study, we used immunohistochemistry (IHC) to determine the prognostic values of multiple tissue biomarkers in hormone-naοve prostatectomy specimens of prostate cancer. Using 510 prostatectomy specimens collected between 2002 and 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
3
2
1
Order By: Relevance
“…Ki-67 appeared to be negative prognostic factor for patients' BRFS, but only in univariate analysis. In multivariate analysis however, we could not confirm its prognostic value which is in agreement with some authors results [9,10] though in disagreement with other studies where prognostic value of Ki-67, among others, but not hypoxic biomarkers were indicated [7]. We suggest, after other authors, that hypoxia in PCa might have more predictive power than proliferation [6].…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Ki-67 appeared to be negative prognostic factor for patients' BRFS, but only in univariate analysis. In multivariate analysis however, we could not confirm its prognostic value which is in agreement with some authors results [9,10] though in disagreement with other studies where prognostic value of Ki-67, among others, but not hypoxic biomarkers were indicated [7]. We suggest, after other authors, that hypoxia in PCa might have more predictive power than proliferation [6].…”
Section: Discussioncontrasting
confidence: 95%
“…Also median time to BR of 35 (range 8.00-86.0) months was similar as in other reports after RP [7,9,13] or after RT (68.9%) [20]. Our study indicated that GS and pT stage were not useful predictive factors for BRFS which may be in agreement with some studies [6] although in contrast with other [7]. This discrepancy in the statistical power of clinicopathological variables maybe caused by different inclusion criteria in other studies, analysis of bigger patients population with advanced and G4 tumours, too short follow-up or use of different levels for PSA BR (np.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations